1994
DOI: 10.1016/0014-5793(94)80563-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective amylin antagonist suppresses rise in plasma lactate after intravenous glucose in the rat

Abstract: Data presented here provide the first demonstration that circulating amylin regulates metabolism in vivo, and support an endocrine hormonal role that is distinct from its autocrine action at pancreatic islets. When rats were pre-treated with the potent amylin antagonist AC187 (n = 18), and then administered a 2 mm01 glucose load, the rise in plasma lactate was less than in rats administered glucose only (n = 27; P < 0.02). When rats were treated so that plasma glucose and insulin profiles were similar (n = 8),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…N-terminally truncated antagonist fragments of sCT, human calcitonin (hCT), rAmy, h␣CGRP, and human AM were used as competitors. Binding of AMY receptor antagonist peptides AC413 and AC187 (42) and an antagonist fragment (residues 8 -37) of the diabetes drug pramlintide (43) were also evaluated. Hereafter, we refer to the recombinant fusion proteins without the use of "MBP" for simplicity.…”
Section: Calcitonin Family Peptide Binding Profiles Of Purified Ctr Ementioning
confidence: 99%
“…N-terminally truncated antagonist fragments of sCT, human calcitonin (hCT), rAmy, h␣CGRP, and human AM were used as competitors. Binding of AMY receptor antagonist peptides AC413 and AC187 (42) and an antagonist fragment (residues 8 -37) of the diabetes drug pramlintide (43) were also evaluated. Hereafter, we refer to the recombinant fusion proteins without the use of "MBP" for simplicity.…”
Section: Calcitonin Family Peptide Binding Profiles Of Purified Ctr Ementioning
confidence: 99%
“…According to animal studies, IAPP may play a role for insulin resistance in rats (13)(14)(15) and dogs (16), while its importance for glucose metabolism in humans is currently being investigated. Islet amyloid polypeptide has been proposed to be a pathogenic factor in noninsulin-dependent diabetes mellitus (17) and an inverse correlation has been reported between the IAPP/insulin ratio and glucose disposal in obese man (18), while in another study, no correlation could be found between an insulin sensitivity index and IAPP release (19).…”
Section: Discussionmentioning
confidence: 99%
“…Human amylin and AC 187, an amylin receptor antagonist (AcVal-Leu-Gly-Lys-Leu-Ser-Gln-Glu-Leu-His-Lys-Leu-Gln-Thr-TyrPro-Arg-Thr-Asn-Thr-Gly-Ser-Asn-Thr-Tyr-NH 2 ) (Young et al 1994), were obtained from SynPep (Dublin, CA), A␤ 25-35 from QCB Biosource International (Camarillo, CA), and iberiotoxin from Sigma Chemical (St. Louis, MO). All the agents were dissolved in distilled water to make 1,000ϫ stock solution (stored at Ϫ70°C) and diluted in external perfusing medium just before the time of application.…”
Section: Drugs and Solutionsmentioning
confidence: 99%